2009
DOI: 10.1007/s00520-009-0752-x
|View full text |Cite
|
Sign up to set email alerts
|

Bereaved cancer carers’ experience of and preference for palliative care

Abstract: This study has provided information on the meaning of palliative care to carers who have had the experience of caring for a patient who died. Carers were uncertain about the role of palliative care and associated it with end-of-life care. Education could help de-stigmatise palliative care and reduce misgivings regarding its introduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 22 publications
(26 reference statements)
3
28
0
3
Order By: Relevance
“…117,118 In a qualitative study of bereaved caregivers of cancer patients, caregivers recommended that palliative care is introduced when patients have uncontrolled symptoms or require assistance at home, further emphasizing the need for additional resources at these time points. 119 Additional efforts to individualize support may more appropriately address caregiver strain. 120 Caregivers of patients with HF noted that their personal health was compromised after recent patient hospitalizations, demonstrating the impact of patient outcomes on caregiver outcomes.…”
Section: Caregiver Outcomesmentioning
confidence: 99%
“…117,118 In a qualitative study of bereaved caregivers of cancer patients, caregivers recommended that palliative care is introduced when patients have uncontrolled symptoms or require assistance at home, further emphasizing the need for additional resources at these time points. 119 Additional efforts to individualize support may more appropriately address caregiver strain. 120 Caregivers of patients with HF noted that their personal health was compromised after recent patient hospitalizations, demonstrating the impact of patient outcomes on caregiver outcomes.…”
Section: Caregiver Outcomesmentioning
confidence: 99%
“…134 There was no doubt that researchers were attempting to address research gaps and made convincing arguments for the need for their research. These articles contributed to the wider knowledge base in terms of understanding more about users' experiences of a service 136 and offering implications for clinical practice. 132,135 There was even an indication in one article that drawing on the trial as a sampling frame for the qualitative research strengthened the research because of the ability to use the large geographical spread of trial participants which would not be feasible in a separately funded qualitative study.…”
Section: Experience Of the Disease Health Behaviour Or Beliefsmentioning
confidence: 99%
“…It may also be important to reflect on sampling from different arms of the RCT both when planning the best sampling strategy for the study and when analysing the qualitative data because one group of authors who used both intervention and control participants expressed concerns about having two groups within their sample with very different experiences. 136 ii. Consider the influence of the trial on the findings.…”
Section: Systematic Mapping Review Of Published Qualitative Research mentioning
confidence: 99%
See 1 more Smart Citation
“…35 An Australian qualitative study found that carers valued the reassurance, information, and education provided by the palliative care nurses. 36 A review of the literature on carer needs for practical support in end-of-life cancer care found that studies consistently reported the need for practical nursing support and nursing-based information; the need for carer education and training related to medication management and symptom control was particularly prominent. 37 One of the approaches that can be used to assess strengths of preference for attributes of goods or services is conjoint analysis or discrete choice experiments (DCEs).…”
mentioning
confidence: 99%